Amyloid β induces hormetic-like effects through major stress pathways in a C. elegans model of Alzheimer’s Disease - James D. Lichty; Hrishikesh Mane; Victoria R. Yarmey; Adriana San Miguel (PLoS ONE, 2025)
Amyloid β (Aβ) is a peptide known for its characteristic aggregates in Alzheimer’s Disease and its ability to induce a wide range of detrimental effects in various model systems. However, Aβ has also been shown to induce some beneficial effects, such as antimicrobial properties against pathogens. In this work, we explore the influence of Aβ in stress resistance in a C. elegans model of Alzheimer’s Disease. We found that C. elegans that express human Aβ exhibit increased resistance to heat and anoxia, but not to oxidative stress. This beneficial effect of Aβ was driven from Aβ in neurons, where the level of induction of Aβ expression correlated with stress resistance levels. Transcriptomic analysis revealed that this selective stress resistance was mediated by the Heat Shock Protein (HSPs) family of genes. Furthermore, neuropeptide signaling was necessary for Aβ to induce stress resistance, suggesting neuroendocrine signaling plays a major role in activating organismal stress response pathways. These results highlight the potential beneficial role of Aβ in cellular function, as well as its complex effects on cellular and organismal physiology that must be considered when using C. elegans as a model for Alzheimer’s Disease.